Effects of on-plane wrist release style on morphological, temporal, and kinematic swing characteristic in golf drives performed by skilled male golfers - Cheng, K.; Mori, K.; Lee, B.; Martinez, A.; Baek, S.; Alvis, H.; Kwon, Y. (Sports Biomechanics, 2025)
A key motion in developing clubhead speed (CHS) during a golf swing is wrist cocking and uncocking on the swing plane. This study aimed to investigate how the morphological, temporal, and kinematic characteristics of drives performed by 84 elite male golfers differ among four distinct wrist release styles (WRS), classified based on the timing of uncocking and the shape of the on-plane wrist angular velocity pattern: Delayed Release 1 and 2 (DR1 and DR2), Early Release (ER), and Recocking (RC). Significant (p < .05) inter-style differences were observed in peak on-plane wrist uncocking velocity, transition and early downswing phase times, directions of the swing plane and hand motion plane, off-plane motions of the hand centre and clubhead, and the transition sequence. The DR styles generally showed larger uncocking velocities, longer transition and shorter early downswing phases, along with a complete proximal-to-distal sequential transition compared to the ER/RC styles. Styles with a prominent negative acceleration phase in the wrist angular velocity (DR1 and RC) exhibited relatively larger off-plane shallowing motions. CHS, however, did not show significant inter-style difference. The WRS reflects variations in backswing pattern (body- vs. arm-driven) and the degree of off-plane shallowing motions of the hands and club.